Exploring Trends in Chemical Education: A Bibliometric Analysis (2019-2024) - Army Auliah; Vika Puji Cahyani (Universitas Negeri Medan, 2024)
A Bibliometric analysis is essential to comprehensively evaluate the progress and impact of chemical education research. The purpose is to analyze the visualization of bibliometric mapping on the network between keys, the most frequently discussed topics, and recommendations for research opportunities on the topic of Chemical Education. This research is quantitative descriptive research with a bibliometric approach. The stages carried out include the data collection process, checking and refilling bibliographic attributes, then bibliometric analysis using VOS viewer software. Data collection is done by searching for Scopus indexed journal articles through Publish or Perish (PoP). Data from Publish or Perish (PoP) is filled in and completed in the author keywords section manually using desktop Mendeley software then integrated into the VOS viewer software for mapping. The results of the analysis of keyword mapping in Scopus indexed scientific articles from 2019-2024, it is known that in the last 5 years, in Scopus indexed journals there are 462 different keywords and form 2072 connecting lines and 35 clusters. The keywords with the strongest links based on VOS viewer include: chemistry education (27), first-year undergraduate/general (25), curriculum (22), general public (20), green chemistry (18), systems thinking (18), high school/introductory chemistry (16), upper-division undergraduate (14).